Implementasi Analytic Hierarchy Process untuk Pengukuran Lean Service di Universitas Pasir Pengaraian - Utami, Urfi; Sabri, Khairul (JURNAL FASILKOM, 2024)
The increasingly competitive environment in higher education forces universities to innovate to survive and enhance their competitiveness. Lean Service, a management concept focused on efficiency and waste reduction, has been proven to improve service quality at a lower cost. This study aims to measure Lean Service at Universitas Pasir Pengaraian using the Analytical Hierarchy Process (AHP). This method is selected due to its ability to objectively assess criteria and alternatives. The study uses six main criteria: quality of academic services, quality of administrative services, availability of facilities, time management efficiency, student satisfaction, and waste reduction. The alternatives analyzed include academic services, administrative services, library and IT, campus facilities, and financial and payment services. The results show that academic services are the best alternative for implementing Lean Service at Universitas Pasir Pengaraian. The implementation of Lean Service is expected to improve management efficiency and service quality at the university.